Biodegradable Nanocomposite Filament Based on PLA/PCL/CNCs for FDM 3D Printing: Production, Characterization and Printability - Ilhan, Recep; Gumus, Omer Yunus; Lekesiz, Huseyin (Wiley, 2025)
Additive manufacturing (AM) is a widening technique for the processing of polymers that is not only used by personal users but also by some industries. The development of biodegradable and bio-based composites for AM attracts great interest with respect to various aspects such as environmental issues, user health, and biomedical applications. Polylactic acid (PLA) is a good candidate for bio-based materials. However, its brittleness needs to be improved. In this study, PLA-based filaments with improved toughness by adding polycaprolactone (PCL) (10% and 20% by weight) and cellulose nanocrystals (CNCs) (5% by weight) were produced for the fused deposition modeling (FDM) technique. The physical, thermal, morphological, and mechanical properties of the produced filaments were comprehensively characterized. All filament diameters were found to be within the suitable range for FDM applications (1.75 +/- 0.05 mm). TGA analyses showed that the filaments could maintain their thermal stability up to approximately 256 degrees C and that the CNCs enhanced their thermal stability. The addition of PCL and CNCs did not cause significant changes in T g and T m of the neat PLA (T g = 58.14 degrees C and T m = 175.93 degrees C). The tensile test results indicated that the PCL and CNCs reinforcement increased the elongation at break from 6.76% to 40.25% and the toughness from 2.94 to 14.48 MJ/m3. In the last part, the three-dimensional (3D) printability was demonstrated by producing auxetic sheets with optimized printing parameters based on MFI, TGA, and DSC data, and good dimensional stability was obtained.
Keywords: 3D printing; 3D printing filaments; cellulose nanocrystals; fused deposition modeling; nanocomposite; polycaprolactone; polylactic acid